2011
DOI: 10.1098/rsbl.2011.0057
|View full text |Cite
|
Sign up to set email alerts
|

The biomechanics of fast prey capture in aquatic bladderworts

Abstract: Carnivorous plants match their animal prey for speed of movements and hence offer fascinating insights into the evolution of fast movements in plants. Here, we describe the mechanics of prey capture in aquatic bladderworts Utricularia stellaris, which prey on swimming insect larvae or nematodes to supplement their nitrogen intake. The closed Utricularia bladder develops lowerthan-ambient internal pressures by pumping out water from the bladder and thus setting up an elastic instability in bladder walls. When t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
47
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 17 publications
3
47
0
Order By: Relevance
“…The pressure inside the door was decreased slowly with respect to the pressure outside. For a Young's modulus E close to 3 MPa, we observed that the door deforms very little up to a pressure difference of about 16 kPa, in agreement with experimental results (Sydenham and Findlay 1973;Sibaoka 1985a, 1985b), while for larger pressure differences, the panel buckles, slides on the threshold and finally swings wide open Singh et al 2011). Figure 3(g) shows the first indentation that appears in the panel, while Figure 3(h) shows the panel opening wide.…”
Section: Snap-buckling As a Speed Boostersupporting
confidence: 76%
See 1 more Smart Citation
“…The pressure inside the door was decreased slowly with respect to the pressure outside. For a Young's modulus E close to 3 MPa, we observed that the door deforms very little up to a pressure difference of about 16 kPa, in agreement with experimental results (Sydenham and Findlay 1973;Sibaoka 1985a, 1985b), while for larger pressure differences, the panel buckles, slides on the threshold and finally swings wide open Singh et al 2011). Figure 3(g) shows the first indentation that appears in the panel, while Figure 3(h) shows the panel opening wide.…”
Section: Snap-buckling As a Speed Boostersupporting
confidence: 76%
“…Highspeed videos show that opening of the door is exceedingly fast. For example, Figures 3(c)-3(e) indicate that it takes less than 1 ms for the panel of an Utricularia australis trap to switch from the closed to the open configuration Vincent et al, 2011) -and yet the traps of U. australis certainly do not belong to the fastest ones of the Utricularia species (see also Singh et al (2011)). Closer examination of Figure 3(d) suggests that the swinging of the panel is preceded by localized curvature inversion and that the door therefore acts as a flexible valve that buckles under the effect of pressure forces rather than as a panel articulated on hinges.…”
Section: Snap-buckling As a Speed Boostermentioning
confidence: 99%
“…Future attempts could either try to record the underpressure values inside the bladders simultaneously to the prey capture experiments (cf. refs 5, 6, 12 and 23), or attempt to evaluate suction dynamics by analyzing spontaneous firings, i.e. firings at trap states of critical underpressure without prey touching the trigger hairs.…”
Section: Discussionmentioning
confidence: 99%
“…At the organismal level, flexibility enhances structural performance, for example by enabling animal bones and plant branches to absorb mechanical energy 10 . Flexibility also underpins a host of dynamic life functions, including locomotion, reproduction and predation, by enabling the storage and swift release of elastic energy, a mechanism used by jumping froghoppers to escape predators 11 , by plants to catapult seeds for dispersal 12 , and by aquatic invertebrates to suck in prey 13 . An extreme consequence of flexibility is the occurrence of mechanical instabilities, such as buckling and fluttering, which in engineered systems are synonymous with failure 14 , but in natural systems can serve functional purpose.…”
mentioning
confidence: 99%